Indians and Leftists in the Making of Ecuador's Modern Indigenous Movements - Becker, Marc (Professor of history) (Book collections on Project MUSE., 2008)
In 1990, indigenous peoples shocked Ecuadorian elites with a powerful uprising that paralysed the country for a week. While the insurrection seemed to come out of nowhere, Marc Becker demonstrates here that it emerged out of years of organising and developing strategies to advance indigenous rights.